The genetic technologies questionnaire in the Greek-speaking population: the moral judgement of the lay public - Melchior, Florian; Angelidou, Ioanna Antigoni; Chorianopoulou, Maria; Teichmann, Birgit (Frontiers in Genetics, 2025)
IntroductionAdvancements in life sciences have significantly boosted biomedical capabilities. Genetic testing forecasts hereditary traits and disease susceptibility, while CRISPR/Cas allows permanent genome alterations. However, ethical considerations arise regarding the morality of these capabilities, particularly concerning the moral status, autonomy, and privacy of living beings. The lack of valid instruments to assess moral judgment in genetic technologies highlights the need for this study, aiming to translate and validate the “Genetic Technologies Questionnaire” (GTQ) and the short version of the “Conventional Technologies Questionnaire” (CTQ5) into Greek. As the full version of the GTQ with 30 questions could be too extensive for some studies, we also tested other versions: The short versions GTQ20-GR and GTQ5-GR which were already presented in the original study, as well as a version which included questions solely about humans (GTQ-H-GR) and is intended for use in human research and therapy, and the GTQ-Moral Status (GTQ-MS-GR), which included questions about genetic testing and gene editing in different living beings to investigate differences in moral status.MethodsA cross-sectional study involved 250 participants who completed an online questionnaire, assessing internal consistency, structural validity, known-groups validity, floor/ceiling effects, and retest reliability (subset of 50 participants). Correlational analyses explored relationships with education, age, genetic knowledge, religiosity, and genetic testing experience. The study followed the STROBE checklist for reporting.ResultsThe GTQ-GR (Cronbach’s α = 0.929) and GTQ20-GR (α = 0.935) exhibit high reliability and stability in assessing moral judgment among lay people, whereas the GTQ5-GR (α = 0.866) and CTQ5-GR (α = 0.758) displayed some weaknesses. Participants tended to rate conventional technologies more favorably than genetic technologies, with genetic testing perceived more positively than genome editing. The two additional derived versions, GTQ-H-GR (α = 0.859) and GTQ-MS-GR (α = 0.787), also demonstrated solid psychometric characteristics.ConclusionThe GTQ-GR is a valid and reliable questionnaire with strong psychometric properties and is now available in Greek.